Fragmented fatherland : immigration and Cold War conflict in the Federal Republic of Germany, 1945-1980 - Clarkson, Alexander, 1977- (Monographs in German history, 2013)
1945 to 1980 marks an extensive period of mass migration of students, refugees, ex-soldiers, and workers from an extraordinarily wide range of countries to West Germany. Turkish, Kurdish, and Italian groups have been studied extensively, and while this book uses these groups as points of comparison, it focuses on ethnic communities of varying social structures-from Spain, Iran, Ukraine, Greece, Croatia, and Algeria-and examines the interaction between immigrant networks and West German state institutions as well as the ways in which patterns of cooperation and conflict differ. This study de.